Neuro-Endocrine Control of Reproduction in Hermaphroditic Freshwater Snails: Mechanisms and Evolution - Koene, Joris M. (Frontiers in Behavioral Neuroscience, 2010)
Invertebrates are used extensively as model species to investigate neuro-endocrine processes regulating behaviours, and many of these processes may be extrapolated to vertebrates. However, when it comes to reproductive processes, many of these model species differ notably in their mode of reproduction. A point in case are simultaneously hermaphroditic molluscs. In this review I aim to achieve two things. On the one hand, I provide a comprehensive overview of the neuro-endocrine control of male and female reproductive processes in freshwater snails. Even though the focus will necessarily be on Lymnaea stagnalis, since this is the best-studied species in this respect, extensions to other species are made wherever possible. On the other hand, I will place these findings in the actual context of the whole animal, after all these are simultaneous hermaphrodites. By considering the hermaphroditic situation, I uncover a numbers of possible links between the regulation of the two reproductive systems that are present within this animal, and suggest a few possible mechanisms via which this animal can effectively switch between the two sexual roles in the flexible way that it does. Evidently, this opens up a number of new research questions and areas that explicitly integrate knowledge about behavioural decisions (e.g., mating, insemination, egg laying) and sexual selection processes (e.g., mate choice, sperm allocation) with the actual underlying neuronal and endocrine mechanisms required for these processes to act and function effectively.